2020
DOI: 10.3390/ceramics3040040
|View full text |Cite
|
Sign up to set email alerts
|

Production of Transparent Soda-Lime Glass from Rice Husk Containing Iron and Manganese Impurities

Abstract: Glass is a familiar material that requires abundant mineral sources, with devastating consequences for the environment. Rice husk ash (RHA) presents a very high silica content (>95%) and it can be a very promising alternative source for silica in silica-based glass. However, impurities like manganese and iron, which depend on the rice harvest, might limit RHA use, particularly in the production of optical transparent glasses. In this work, we discussed how Mn and Fe can affect the coloring of the produced g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…For RHA, it is observed that, in addition to the presence of a high silica content, which makes it a suitable material for the production of silicabased glasses, other oxides are present. In particular, it was observed in another work that small amounts of manganese ions can cause an absorption around 480 nm, leaving the glass with a reddish color 21,31 . Actually, the absorbance at 480nm is an effect of the manganese 3+ oxidation state 21 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For RHA, it is observed that, in addition to the presence of a high silica content, which makes it a suitable material for the production of silicabased glasses, other oxides are present. In particular, it was observed in another work that small amounts of manganese ions can cause an absorption around 480 nm, leaving the glass with a reddish color 21,31 . Actually, the absorbance at 480nm is an effect of the manganese 3+ oxidation state 21 .…”
Section: Resultsmentioning
confidence: 99%
“…In particular, it was observed in another work that small amounts of manganese ions can cause an absorption around 480 nm, leaving the glass with a reddish color 21,31 . Actually, the absorbance at 480nm is an effect of the manganese 3+ oxidation state 21 . According to the literature, antimony trioxide can react with the metallic ions of manganese at high temperatures, by the following redox reaction 32 : Sb 3+ + 2Mn 3+ → 2Mn 2+ + Sb 5+ , reducing Mn 3+ to Mn 2+ inside the glass matrix, enabling to obtain transparent glasses in the visible region.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…and rice straw ashes (RSA). Other works demonstrated that RHA can be reused in the manufacture of innovative materials, such as glass (Gonçalves, 2020), ceramic and cement materials (Hossain, 2018) mainly due to its silica composition, and as an adsorbent for water purification (Abaide, 2019;Ahmaruzzaman, 2011).…”
Section: Introductionmentioning
confidence: 99%